Homozygosis of Bt locus increases Bt protein expression and the control of Spodoptera frugiperda (Lepidoptera: Noctuidae) in maize hybrids - Eghrari, Kian [UNESP]; Humberto de Brito, André; Baldassi, Amanda [UNESP]; Balbuena, Tiago Santana [UNESP]; Fernandes, Odair Aparecido [UNESP]; Môro, Gustavo Vitti [UNESP] (Elsevier, 2019)
Spodoptera frugiperda (J.E. Smith) is the main pest of maize in Brazil and its control has been targeted by Bt maize hybrids. Generally, Bt maize hybrids possess the transgenic locus in a hemizygous condition, that is, containing only one copy of the Bt allele. However, studies have shown that maize hybrids with an additional transgenic allele, namely, in a homozygous state, increases transgenic protein expression. Our aim in this study was to evaluate whether the transgenic event TC1507 x MON89034 x NK603 in homozygosis increases Bt protein expression levels and, consequently, reduces S. frugiperda leaf-feeding injury and larval survival which affects maize grain yield. Leaf-feeding injury of S. frugiperda was 29% lower on homozygous hybrids relative to their isogenic hemizygous versions. Isogenic homozygous and hemizygous hybrids did not differ in grain yield in this study. S. frugiperda survivorship on homozygous hybrids was significantly lower than on their hemizygous isogenic versions (16.9% and 38.5%, respectively). Homozygous hybrids presented higher Cry1F, Cry1A.105, and Cry2Ab2 protein expression levels relative to their isogenic hemizygous versions (approximately 1.5-, 2.0-, and 2.5-fold, respectively). The Bt maize event TC1507 x MON89034 x NK603 in a homozygous state increases Bt protein expression levels and the control of S. frugiperda. Therefore, the deployment of homozygous transgenic maize hybrids to farmers is more desirable than the hemizygous versions.
Keywords: Bt protein concentration; Fall armyworm; Resistance management; Zygosity